Perceived harms and protective behavioural strategies among khat chewers: a qualitative study in Jimma, Ethiopia - Amanti Baru Olani; Tom Decorte (BMC, 2023)
Abstract Background While there have been many previous studies focusing on the adverse effects of khat chewing, attempts to investigate the protective behavioural strategies (PBS) employed by the khat using population are rare. PBS are strategies that substance users employ to minimize or alleviate the possible negative consequences related to the behaviour. This study focuses on the harms that chewers associate with khat use, and the behavioural strategies they practise to prevent or minimize these harms. Methods A community-based qualitative study was conducted using a snowball sampling technique to recruit a diverse sample of khat chewing participants (N = 102) in Jimma city, Ethiopia. Face-to-face in-depth interviews were carried out with the participants. Results Participants identified a variety of harms likely to result from chewing khat. These include impacts on their finances, work, social life and health. The PBS that participants employed to avoid or minimize the risks were classified into four themes based on their temporal sequence with khat chewing sessions: prior to chewing, during chewing, after chewing and general PBS covering the whole of their khat chewing career. The PBS enable khat chewers to prevent or minimize the adverse health consequences of chewing, socialize and work without or with fewer difficulties and manage their economy successfully. Conclusion The study participants believe that khat-related harms are avoidable if khat users implement appropriate strategies prior to, during and after chewing, and if they apply PBS to khat-related factors (e.g. type, amount and frequency), set factors (e.g. reason for using and health behaviour) and setting factors (e.g. place of use, when used, with whom used and social norms) covering the whole of their khat chewing career.